2015
DOI: 10.3389/fonc.2015.00257
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Telomerase in the Radiation Response: Implications for Instability, Reprograming, and Carcinogenesis

Abstract: Telomeres are nucleoprotein complexes comprised of tandem arrays of repetitive DNA sequence that serve to protect chromosomal termini from inappropriate degradation, as well as to prevent these natural DNA ends from being recognized as broken DNA (double-strand breaks) and triggering of inappropriate DNA damage responses. Preservation of telomere length requires telomerase, the specialized reverse transcriptase capable of maintaining telomere length via template-mediated addition of telomeric repeats onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 99 publications
(105 reference statements)
4
36
0
Order By: Relevance
“…Here, we hypothesized a priori that inclusion of inversions could improve retrospective biodosimetry for estimating exposures that took place over six decades in the past, reasoning that their persistence and higher induction rate per unit dose would be favorable for retrospective dose estimation. Furthermore, we hypothesized that changes in telomere length [e.g., shortening, see (35)] might also reflect these past radiation exposures, thereby providing insight into potential long-term biological and overall health implications [see (12)]. These considerations were the basis for the design of an assessment based on both inversions and translocations.…”
Section: Biodosimetry (Methods 3)mentioning
confidence: 99%
“…Here, we hypothesized a priori that inclusion of inversions could improve retrospective biodosimetry for estimating exposures that took place over six decades in the past, reasoning that their persistence and higher induction rate per unit dose would be favorable for retrospective dose estimation. Furthermore, we hypothesized that changes in telomere length [e.g., shortening, see (35)] might also reflect these past radiation exposures, thereby providing insight into potential long-term biological and overall health implications [see (12)]. These considerations were the basis for the design of an assessment based on both inversions and translocations.…”
Section: Biodosimetry (Methods 3)mentioning
confidence: 99%
“…Telomerase inhibition is thus widely considered as an attractive strategy in cancer therapy . Telomerase dysfunction and telomere length also strongly influence the response of organisms, cells and genomes to the action of ionizing radiation . In living cells, dTTAGGG repetitions in the single‐stranded 3′ overhang can fold into stable four‐stranded G‐quadruplex structures with a high propensity.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported an increase in telomerase activity with radiation exposure ( Hande et al, 1998 ; Leteurtre et al, 1997 ). This induction appears to be cell type specific ( Finnon et al, 2000 ; Sishc et al, 2015 ) and exhibits dose-dependence and temporal kinetics. Increase in activity has been noted as early as 0.5 h and up to 24 h following exposure of fibroblasts and lymphoblasts to low-LET radiation.…”
Section: Telomere Dysfunction and Carcinogenesismentioning
confidence: 99%
“…Recent studies have shown that reactivation of telomerase can trigger cellular reprogramming and enrichment of putative stem cell populations post radiation exposure ( Sishc et al, 2015 ). The contribution of the mean telomere length, the length of the shortest telomere, and the degree of telomerase activation that drives these cell fate decisions is unclear.…”
Section: Telomere Dysfunction and Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation